Religion, gambling attitudes and corporate innovation - Adhikari, Binay Kumar; Agrawal, Anup (Journal of Corporate Finance, 2016)
We find that firms headquartered in areas with a taste for gambling tend to be more innovative, i.e. they spend more on R&D, and obtain more and better quality patents. These results are supported by several robustness checks, tests to mitigate identification concerns, and analyses of several secondary implications. Investment in innovation makes a stock more lottery-like, a feature desired by individuals with a taste for gambling. Gambling preferences of both local investors and managers appear to influence firms' innovative endeavors and facilitate transforming their industry growth opportunities into firm value.